26. QUALITY OF INPATIENT SERVICES IN CHAU THANH DISTRICT HEALTH CENTER, LONG AN PROVINCE IN 2023 (Tạp chí Y học Cộng đồng, 2025)
Introduction: Service quality is a crucial factor influencing patients' decisions to utilize medical services. This study aims to describe the service quality of the inpatient care in the studied hospital.Methods: We employed a cross-sectional design (mixed-methods approach using quantitative and qualitative surveys) in the three clinical faculties of Chau Thanh District Health Center in 2023. The quantitative survey was done using a self-administered interview with 300 inpatients. A qualitative survey was conducted with 26 informants, comprising two in-depth interviews and four focus group discussions with health providers and inpatients.Findings: Quality service is assessed at a reasonable level, with an average score of 4.03 points, and a rate of good or better evaluations of 73.8%. All five dimensions have an average service quality of over 3.96 points. The two dimensions with the lowest points were empathy (3.97 points with 76% rating as good or better) and tangible means (3.96 points with 76% rating as good or better). The remaining three dimensions were rated higher, specifically responsiveness (4.09 points, with 78.7% rating as good or better), assurance (4.08 points, with 76% rating as good or better), and reliability (4.06 points, with 79% rating as good or better).Conclusion: The quality is good, as assessed by the patient. The study results recommend developing a plan to recruit human resources, utilizing an online app for patient counseling and communication, and providing incentives for highly specialized staff.
Keywords: Service quality; inpatient; Chau Thanh District Health Center.